Giant African Land Snail, Achatina fulica in Udaipur, Rajasthan: A Threat to Biodiversity and Ecosystem - Choubisa, Shanti Lal; Sheikh, Zulfiya (Asian Journal of Biological and Life Sciences, 2013)
During survey of terrestrial and aquatic snail fauna in southern Rajasthan, a number of giant African snails Achatina fulica Bowdich, were recovered from Din Dayal Upadhyay garden in Udaipur. This garden is situated in close proximity with Lake Pichhola that provides a humid environment which is preferred by this land snail species. It was seen in huge numbers feeding on Hibiscus plants that are abundant in this place. Even the rock crevices were inhabited by Achatina. This exotic giant land snail is becoming a threat to the existing ecosystem by destroying the crops, plants and disturbing food chain which are discussed.